Limites ao uso da tecnologia no monitoramento e controle de gestão do trabalhador em regime de teletrabalho - Slosbergas, Luciana Barcellos (2024)
The technological evolution has generated significant impacts in the field of Labor Law. Telecommuting emerged in the 1970s and gained prominence due to the breaking down of borders and the globalization of the economy. New forms of work stemming from the Fourth Industrial Revolution have substantially influenced labor relations. The COVID-19 pandemic accelerated the digitization of work relationships, highlighting telecommuting as the primary tool during the period of social isolation. Post-pandemic, companies already adapted to this new model began seeking advanced technological solutions to monitor the activity and productivity of telecommuting workers. Despite recent legislative changes, there is a perceived gap in regulations regarding the limits for the use of these technologies, which are susceptible to violating the privacy of the worker. This work aims to highlight that protecting worker in telecommuting represents a challenge for Labor Law, especially due to the inherent complexities of remote work, emphasizing the fundamental right to privacy